Politics and power in 20th-century Japan : The reminiscences of Miyazawa Kiichi - Mikuriya, Takashi (Bloomsbury Academic, 2015)
This is the story, told from the source, of a man who had a profound influence in shaping Japan's postwar economic policy, who was a lifelong moderate and advocate for an internationalist approach, and who was both first-hand witness and pivotal actor in so many of the events that have forged contemporary Japan.